Prepreg composition, prepreg, circuit substrate and printed circuit board
By using dielectric filler and resin composition with a conductivity of less than 450μS/cm and performing surface modification or coating, the ion migration problem of printed circuit boards in high temperature and high humidity environments is solved, and its ion migration resistance is significantly improved. and dielectric properties.
Patent Information
- Application Number
- CN202010503707.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-06-05
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2040-06-05
AI Technical Summary
Printed circuit boards are prone to ion migration in high temperature and high humidity environments, resulting in short-circuit failure. The prior art is difficult to effectively improve their ion migration resistance and there is a risk of defects.
Using dielectric filler and resin compositions with conductivity less than or equal to 450μS/cm, the number of free charged ions on the surface of the dielectric filler is reduced through surface modification or coating technology to form a prepreg composition with low conductivity for preparation The semi-cured sheet and circuit substrate are used to improve the ion migration resistance of printed circuit boards.
It effectively reduces the number of free charged ions in the printed circuit board when in use, improves its ion migration resistance, and optimizes the dielectric constant and dielectric loss, and adjusts the dielectric performance range.
Smart Images

Figure GDA0004439646710000071 
Figure GDA0004439646710000081 
Figure GDA0004439646710000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic industry, in particular to a prepreg composition, a semi-cured sheet, a circuit substrate and a printed circuit board. Background Art
[0002] When working under high temperature and high humidity, the ion migration (CAF) phenomenon of the printed circuit board (PCB) can cause it to short-circuit and fail, which is very harmful.
[0003] There are many factors that affect PCB ion migration, including internal factors such as PCB design structure and material selection, as well as external factors such as processing, storage and working environment. In order to improve the PCB's resistance to ion migration, traditional methods include optimizing the design of PCB structure, preferentially using materials resistant to ion migration, adding ion capture agents, and strictly controlling the PCB processing procedures. However, these methods do not significantly improve the PCB's resistance to ion migration and there is a risk of causing PCB defects. Summary of the invention
[0004] Based on this, it is necessary to provide a prepreg composition, a prepreg, a circuit substrate and a printed circuit board to address the above problems; the printed circuit board obtained based on the prepreg composition has strong ion migration resistance.
[0005] A prepreg composition comprises a resin and a dielectric filler, wherein the electrical conductivity of the dielectric filler is less than or equal to 450 μS / cm.
[0006] In one embodiment, the surface of the dielectric filler has a modification.
[0007] In one embodiment, the modification covers the dielectric filler.
[0008] In one embodiment, the material of the modifier includes at least one of a surfactant, a titanate coupling agent, a silane coupling agent, a fluorosilane coupling agent, and an alcoholamine surface treatment agent.
[0009] In one embodiment, the material of the modifier includes at least one of non-metal oxide, non-metal nitride, and non-metal sulfide.
[0010] In one of the embodiments, the mass ratio of the resin to the dielectric filler is 100:60-100:150.
[0011] In one embodiment, the prepreg composition further includes at least one of a coupling agent and a cross-linking agent.
[0012] A semi-cured sheet comprises a reinforcing material and the above-mentioned prepreg composition attached to the reinforcing material.
[0013] A circuit substrate comprises a dielectric layer and a conductive layer arranged on at least one surface of the dielectric layer, wherein the dielectric layer is formed by curing the above-mentioned prepreg.
[0014] A printed circuit board comprises the above-mentioned circuit substrate.
[0015] In the prepreg composition of the present invention, by controlling the conductivity of the dielectric filler, the number of free charged ions generated by the dielectric filler can be effectively controlled. Therefore, when the PCB made based on the prepreg composition is used, the number of free charged ions generated is small, which effectively improves the ion migration resistance of the PCB. At the same time, the PCB of the present invention has excellent dielectric constant and dielectric loss, and the dielectric performance range is adjustable. DETAILED DESCRIPTION
[0016] The prepreg composition, prepreg, circuit substrate and printed circuit board provided by the present invention will be further described below.
[0017] After long-term and in-depth research, the applicant has found that during the production and processing of dielectric fillers, due to the processing technology and the use of additives, it is inevitable that substances that can hydrolyze to produce free charged ions or substances that can be corroded by acids / alkalis to produce charged ions will remain on the surface. In addition, since borosilicate glass dielectric fillers (such as hollow glass microspheres) contain alkali metal components such as Na2O, K2O, and CaO, the surface is easily corroded during use to produce free charged metal cations. Therefore, during use, affected by the environment, the number of free charged ions inside the PCB will continue to increase, and then the potential difference will continue to increase under the power-on condition, eventually leading to CAF failure of the PCB.
[0018] In short, the ability of dielectric fillers to generate free charged ions is the key factor in determining the number of free charged ions inside the PCB, which in turn determines the PCB's resistance to ion migration. The conductivity of dielectric fillers can reflect the ability of dielectric fillers to generate free charged ions.
[0019] To this end, in a first aspect of the present invention, a prepreg composition is provided. The prepreg composition comprises a resin and a dielectric filler. The electrical conductivity of the dielectric filler is less than or equal to 450 μS / cm.
[0020] It should be noted that the test method for the electrical conductivity of the dielectric filler of the present invention is measured by the following method:
[0021] Method 1:
[0022] 100 mL of deionized water was measured and placed in the first beaker and the second beaker respectively. Temperature compensation was performed to make the conductivity of the deionized water in the first beaker and the second beaker ≤ 2.0 μS / cm. Then 10 g of dielectric filler was accurately weighed and placed in the first beaker. The second beaker was used as a blank control. At the same time, the samples were placed on an electromagnetic stirrer and stirred for 30 minutes to obtain the test sample and the blank sample.
[0023] Method 2:
[0024] 50 mL of deionized water was measured and placed in the first digestion tank and the second digestion tank respectively. Temperature compensation was performed to make the conductivity of the deionized water in the first digestion tank and the second digestion tank ≤ 2.0 μS / cm. Then 5 g of dielectric filler was accurately weighed and added to the first digestion tank. The second digestion tank was used as a blank control. At the same time, they were placed in a constant temperature drying oven at 95°C for 20 hours, then taken out and cooled to room temperature to obtain the test sample and the blank sample.
[0025] Rinse the conductivity tester electrode with the sample to be tested 2-3 times, perform temperature compensation, and measure the conductivity σ1 of the sample to be tested; rinse the electrode with the blank sample 2-3 times, perform temperature compensation, and measure the conductivity σ2 of the blank sample. The conductivity (σ) of the dielectric filler is calculated according to the formula: σ=σ1-σ2, μS / cm.
[0026] Therefore, by controlling the conductivity of the dielectric filler, the number of free charged ions generated by the dielectric filler is effectively controlled, thereby improving the ion migration resistance of the PCB based on the prepreg composition.
[0027] Of course, the lower the conductivity of the dielectric filler, the smaller the number of free charged ions produced. Therefore, it is further preferred that the conductivity of the dielectric filler is less than or equal to 410 μS / cm, or less than or equal to 400 μS / cm, or less than or equal to 350 μS / cm, or less than or equal to 300 μS / cm, or less than or equal to 200 μS / cm, or less than or equal to 100 μS / cm.
[0028] In the present invention, a dielectric filler having an electrical conductivity that meets the above requirements may be selected, or the dielectric filler may be surface treated to meet the above requirements.
[0029] Specifically, the surface treatment method includes: (1) using acid, alkali and other reagents to clean the surface of the dielectric filler to reduce or consume substances on the surface of the dielectric filler that can produce free charged ions; (2) using surface modification, coating and other methods to modify the surface of the dielectric filler to block the surface of the dielectric filler from contacting the outside world, thereby directly avoiding the generation of free charged ions on the surface of the dielectric filler.
[0030] Taking into account that the substances that can produce charged ions on the surface of the dielectric filler are different, in particular, the borosilicate glass-based dielectric filler itself will produce free charged metal cations. Therefore, the present application further prefers to modify the surface of the dielectric filler by surface modification, coating and other methods so that the surface of the dielectric filler has a modified substance, and further preferably, the modified substance partially coats or completely wraps the dielectric filler to block the surface of the dielectric filler from the external base and produce free charged ions.
[0031] In some embodiments, the material of the modifier includes at least one of a surfactant, a titanate coupling agent, a silane coupling agent, a fluorosilane coupling agent, and an alcoholamine surface treatment agent, and further preferably includes a polymer compound with a chain structure that can react with and connect with active groups such as hydroxyl groups on the surface of the dielectric filler, such as: higher fatty acids and lipids, alcohols, amides, metal salts, etc. in surfactants; monoalkoxy type, monoalkoxy pyrophosphate type, coordination type, chelate type, etc. in phthalate coupling agents; vinyl type, amino type, epoxy type, isocyanate type, etc. in silane coupling agents. Acid ester type, methacryloxy type, mercapto type, urea type, etc.; fluorosilane coupling agents such as tridecafluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane, heptadecafluorodecyltrimethoxysilane, heptadecafluorodecyltriethoxysilane, trifluoropropylmethyldimethoxysilane, etc.; ethanolamine, diethanolamine, triethanolamine, triisopropanolamine, N,N'-bis(2-hydroxypropyl)aniline, 2-aminoethanol, 2-dibutylaminoethanol, 2-diethylaminoethanol, polyvinyl alcohol, polydopamine, polyethyleneimine, polyimide, polyamic acid, etc. in alcoholamine surface treatment agents.
[0032] In order to increase the content of the modifier on the surface of the dielectric filler so that the modifier can cover or completely envelop the dielectric filler, the surface of the dielectric filler may be pretreated to increase the content of active groups such as hydroxyl groups on the surface.
[0033] In other embodiments, the material of the modifier may also be inorganic materials such as non-metallic oxides, non-metallic nitrides, non-metallic sulfides, such as silicon dioxide, boron nitride, boron oxide, etc. In this case, the inorganic materials such as silicon dioxide, boron nitride, boron oxide, etc. partially cover or completely cover the dielectric filler to form a composite dielectric filler with a core-shell structure having the dielectric filler as the core and the inorganic materials such as silicon dioxide as the shell. The mass of the shell preferably accounts for 0.1%-30% of the composite dielectric filler, more preferably 1%-20%, and more preferably 5%-10%.
[0034] The absolute value of the difference between the Df of the composite dielectric filler and the dielectric filler is less than or equal to 0.01, thereby not only improving the electrical conductivity of the dielectric filler but also ensuring its dielectric performance.
[0035] Furthermore, compared with organic materials such as surfactants, titanate coupling agents, silane coupling agents, and alcoholamine surface treatment agents, inorganic materials themselves do not produce ion precipitation, and inorganic materials are coated on the surface of dielectric fillers by reaction, high-temperature sintering, etc., and can form a dense coating layer. Therefore, the composite dielectric filler obtained by using inorganic materials as modifiers has lower conductivity.
[0036] In the prepreg composition of the present invention, the mass ratio of the resin to the dielectric filler is 100:60-100:150.
[0037] Specifically, the dielectric filler includes at least one of titanium dioxide, polytetrafluoroethylene, barium titanate, strontium titanate, amorphous silica, spherical silica, corundum, wollastonite, solid glass microspheres, hollow glass microspheres, kaolin, mullite, hollow silica microspheres, hollow titanium dioxide microspheres, synthetic glass, quartz, boron oxide, boron nitride, aluminum nitride, aluminum carbide, beryllium oxide, aluminum oxide, aluminum hydroxide, magnesium oxide, mica, talc, and magnesium hydroxide, and is selected and compounded according to different dielectric performance requirements.
[0038] Specifically, the resin includes at least one of polybutadiene, polyisoprene, modified polybutadiene, copolymers of polybutadiene and styrene, block copolymers or graft copolymers that can undergo copolymerization and cross-linking reactions, thermosetting liquid crystal resins, phenolic resins, cyanate resins, polyphenylene ether resins, maleimide resins, modified polyphenylene ether resins, polyimide resins, phenoloxy resins, polytetrafluoroethylene resins, benzoxazine resins, melamine formaldehyde resins, furan resins, silicone resins, urea-formaldehyde resins, and epoxy resins.
[0039] Furthermore, the prepreg composition further comprises at least one of a curing agent, a coupling agent, and a cross-linking agent. Wherein, based on 100 parts by weight of the resin, the amount of the curing agent is 1 part by weight to 10 parts by weight, the amount of the coupling agent is less than or equal to 5 parts by weight, and the amount of the cross-linking agent is less than or equal to 15 parts by weight.
[0040] Specifically, the curing agent includes at least one of 2,5-dimethyl-2,5-di(benzyl peroxide)hexane, di-tert-butyl peroxide, 2,5-dimethyl-2,5-bis(tert-butyl peroxy)hexane, 2,5-dimethyl-2,5-di-tert-butyl peroxy-3-hexyne, and diethylpropene peroxide; the coupling agent includes at least one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent; the auxiliary cross-linking agent includes at least one of triallyl isocyanurate, triallyl cyanurate, diallyl terephthalate, divinylbenzene, and a multifunctional acrylate.
[0041] The second aspect of the present invention further provides a prepreg, comprising a reinforcing material and the prepreg composition as described above attached to the reinforcing material.
[0042] Wherein, the reinforcing material is preferably glass fiber cloth.
[0043] Specifically, the resin, dielectric filler and curing agent are mixed according to a weight ratio, diluted with a solvent to an appropriate viscosity, and the dielectric filler is evenly dispersed in the resin to prepare a glue solution, and the reinforcing material is impregnated with the above glue solution, and then the solvent is removed to obtain a prepreg.
[0044] According to a third aspect of the present invention, there is provided a circuit substrate, comprising a dielectric layer and a conductive layer disposed on at least one surface of the dielectric layer, wherein the dielectric layer is formed by curing the above-mentioned prepreg.
[0045] Specifically, the number of the prepreg sheets may be one or more. When there are more than one prepreg sheets, the prepreg sheets are stacked and then cured to obtain the dielectric layer.
[0046] The curing temperature is 100℃~300℃, and the curing pressure is 10kg / cm 2 ~80kg / cm 2 During the curing process, the third resin in the mixed resin and the second resin modified on the surface of the filler will react with the first resin to form chemical bonds and polymerize together.
[0047] Specifically, the metal foil is preferably copper foil, thereby obtaining a copper clad laminate.
[0048] The circuit substrate of the invention has excellent dielectric constant and dielectric loss, and the range is adjustable.
[0049] The fourth aspect of the present invention also provides a printed circuit board, including the above-mentioned circuit substrate, which is mainly made by the circuit substrate through processes such as drilling, hole filling, micro-etching, pre-preg, activation, acceleration, chemical copper and copper thickening.
[0050] In the printed circuit board of the present invention, since the electrical conductivity of the dielectric filler in the dielectric layer of the circuit substrate is low, the number of free charged ions generated during use is small, thereby effectively improving the ion migration resistance of the PCB.
[0051] Hereinafter, the prepreg composition, prepreg, circuit substrate and printed circuit board will be further described through the following specific examples.
[0052] Table 1
[0053]
[0054]
[0055] Silica coating method:
[0056] Take 90g of D 50 =25μm hollow glass microspheres, 57mL deionized water and 262mL ethanol were placed in a flask, stirred for 30min under 60℃ water bath heating, and 131mL ethanol solution containing 9.36g tetraethyl orthosilicate (TEOS) and 18.4g ammonia water were slowly added to the flask at the same time in a parallel flow manner, and the slurry concentration was controlled to be 200g / L. The amount of TEOS added was 3% of the mass of the hollow glass microspheres in terms of SiO2, and the concentration of catalyst ammonia water was 4% of the mass of the hollow glass microspheres. The addition was completed in 90min, and after aging for 2h, it was washed with deionized water until the conductivity of the washing liquid was less than 100, and placed in a 100℃ oven for drying for more than 12h to obtain a third dielectric filler.
[0057] Boron oxide coating method:
[0058] Weigh 10 parts by weight of D 50 = 25 μm hollow glass microspheres and 1 part by weight of boron oxide micropowder are placed in a clean container, and a mixed solution of an appropriate amount of ethanol and distilled water in a volume ratio of 3:1 is added, and ultrasonic vibration is performed for 1 to 5 hours and then mechanically stirred for more than 4 hours. After the mixture is completely stirred and mixed, it is placed in a 105°C drying oven for 12 to 24 hours to completely dry, and then calcined in a 700°C muffle furnace for 12 hours to obtain a fourth dielectric filler.
[0059] Surface modification methods:
[0060] First, D 50 = 25μm hollow glass microspheres were placed in deionized water and stirred thoroughly, then left to stand for 2h, and the hollow glass microspheres floating on the upper layer were filtered and dried. Then, 1 part of the hollow glass microspheres and 30 parts of 0.3mol / L sodium hydroxide solution were mixed in a three-necked flask, refluxed and stirred at 80°C for 1.5h, and then the hollow glass microspheres were washed with deionized water until the pH value of the washing liquid was 7, and then dried in a constant temperature drying oven at 100°C after filtration to obtain hydroxylated hollow glass microspheres.
[0061] Take 10 parts by mass of hydroxylated hollow glass microspheres and mix them in 30 parts by mass of 40% to 80% ethanol aqueous solution, add 1 part by mass of surface modifier under stirring at 80°C, continue heating and stirring for 2 hours, then use ethanol to wash away the surface modifier remaining on the surface of the hollow glass microspheres, filter and dry in an oven at 100°C to obtain the fifth, sixth and seventh dielectric fillers.
[0062] Embodiment 1:
[0063] 72 parts by weight of the first resin, 28 parts by weight of the second resin, 40 parts by weight of the first dielectric filler, 20 parts by weight of the third dielectric filler, 1.8 parts of a coupling agent, 3 parts of a curing agent and 10 parts of a cross-linking aid are mixed, adjusted to a suitable viscosity with xylene solvent, stirred and mixed evenly to evenly disperse the dielectric filler in the resin to prepare a glue solution.
[0064] Use 1080 glass fiber cloth to impregnate the above glue and control the weight to 189±3g / m 2 , and then dried to remove the solvent to obtain a non-sticky semi-cured sheet.
[0065] Six prepregs were stacked, and 1 oz thick TZA copper foil was applied on both sides. The prepregs were cured by programmed temperature rise in a high temperature vacuum press with a curing pressure of 60 kg / cm 2 The curing temperature is 170°C, the curing time is 2h, and then the temperature is raised to 270°C and cured for 1h to form a circuit substrate.
[0066] The PCB processing for this circuit substrate includes the following process flow: drilling board → hole filling → micro-etching → pre-preg → activation → acceleration → chemical copper → copper thickening. The dielectric properties test and CAF test are also carried out, and the results are shown in Table 2.
[0067] Among them, the dielectric properties test uses Rosenberg's vector grid analyzer.
[0068] The CAF test method is as follows:
[0069] Place the PCB in an environment of 23±2℃ and 50±5% relative humidity for 30 minutes, and measure its normal insulation resistance with a test voltage of 50±1V DC. Raise the environment to 85±2℃ and 85±3% relative humidity and keep it constant for 96 hours without applying bias voltage. Test the insulation resistance at 50±1V at the 96th hour without applying bias voltage. After 96 hours of constant temperature, apply a 50±1V DC bias voltage and measure the insulation resistance every 1 hour until 500 hours (bias period). During this period, the polarity of the measured voltage and the polarity of the bias voltage remain consistent.
[0070] Embodiment 2 to Embodiment 8
[0071] The manufacturing process is the same as that of Example 1, and the changes in the proportions are shown in Table 2.
[0072] Comparative Example 1 to Comparative Example 3
[0073] The manufacturing process is the same as that of Example 1, and the changes in the proportions are shown in Table 2.
[0074] Table 2
[0075]
[0076]
[0077] It can be seen from Table 2 that the PCB using dielectric fillers with a conductivity lower than 450 μS / cm has significantly improved ion migration resistance. Among them, Comparative Example 3 cannot be pressed into a board for testing due to excessive glue flow.
[0078] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0079] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A prepreg composition, characterized in that The prepreg composition comprises a resin and a dielectric filler, wherein the electrical conductivity of the dielectric filler is less than or equal to 450 μS / cm, wherein a modifier is provided on the surface of the dielectric filler, the modifier covers the dielectric filler, and the material of the modifier is selected from an inorganic material, and the inorganic material comprises at least one of a non-metallic oxide, a non-metallic nitride, and a non-metallic sulfide; The dielectric filler includes at least one of titanium dioxide, polytetrafluoroethylene, barium titanate, strontium titanate, corundum, wollastonite, solid glass microspheres, hollow glass microspheres, kaolin, mullite, hollow titanium dioxide microspheres, synthetic glass, quartz, boron oxide, boron nitride, aluminum nitride, aluminum carbide, beryllium oxide, aluminum oxide, aluminum hydroxide, magnesium oxide, mica, talc, and magnesium hydroxide.
2. The prepreg composition according to claim 1, characterized in that The modifier covers the dielectric filler to form a composite dielectric filler with a core-shell structure having the dielectric filler as the core and the inorganic material as the shell layer, wherein the mass of the shell layer accounts for 0.1%-30% of the composite dielectric filler.
3. The prepreg composition according to claim 1, characterized in that The mass ratio of the resin to the dielectric filler is 100:60-100:
150.
4. The prepreg composition according to claim 1, characterized in that The prepreg composition further comprises at least one of a curing agent, a coupling agent and a cross-linking aid.
5. A prepreg, characterized in that: A prepreg composition comprising a reinforcing material and attached to the reinforcing material as claimed in any one of claims 1 to 4.
6. A circuit substrate, characterized in that: The invention comprises a dielectric layer and a conductive layer arranged on at least one surface of the dielectric layer, wherein the dielectric layer is formed by curing the prepreg according to claim 5.
7. A printed circuit board, characterized in that: Includes the circuit substrate as claimed in claim 6.
Citation Information
Patent Citations
Packing in metal-clad foil plate with low thermal expansion coefficient and preparation method of packing
CN103360621A
Low coefficient of thermal expansion thermosetting resin composite, preimpregnated material and metal foil-clad plate
CN103360724A
Ion-migration-resistant filler and copper clad plate
CN106633648A
Thermosetting resin composition, prepreg, laminate and printed circuit board
CN109135193A
Vinyl thermosetting resin composition, prepreg, laminated board and printed circuit board
CN109836631A